SCENARIO PLANNING FOR PT BANGGAI LNG'S BUSINESS STRATEGY TO FACE FUTURE LNG INDUSTRY CHALLENGES - Christian, Rio (ULTIMA Management, 2024)
Abstract- The liquefied natural gas (LNG) industry is undergoing significant transformation due to fluctuating global demand, the transition to renewable energy, and evolving regulations. PT Banggai LNG (PT BLNG), a key player in Indonesia, leverages its strategic location and advanced infrastructure to meet domestic and international demand. However, PT BLNG faces market volatility, intense competition, and increasingly complex environmental regulations. This research employs scenario planning to help PT BLNG develop business strategies to address challenges in the LNG industry, utilizing PESTEL analysis, Porter's Five Forces, VRIO framework, and SWOT analysis. These analyses highlight regulatory pressures, competition, limited resources, and regional demand opportunities. Four strategic scenarios were developed: "Stable but Limited Growth,” "Emerging Markets,” "Challenging Markets,” and "Profitable but Constrained Markets.” Proposed strategies include cost optimization, infrastructure development, and market diversification. With early warning signals, a five-year roadmap, and the four strategic scenarios, PT BLNG is expected to adapt to uncertainties, align with global energy trends, and sustain its long-term competitiveness in the LNG industry in Indonesia and the surrounding region. Keywords: Business Strategy; Liquefied Natural Gas; Scenario Planning